PRODUCT DESIGN IMPROVEMENT AND DEVELOPMENT TRAINING FOR BAG PRODUCTS AT SME JMS LEATHER - Sylvia, Sylvia; Monica , Christiana Gracia; Febrianus, Justin; Ofel Boas , William; Mercyo, Steve; Suhardi, Steven (Universitas Pelita Harapan, 2025)
JMS Leather is a small medium enterprise that produces leather products such as bags, wallets, book covers and accessories. It has challenges such as the lack of unique and innovative products that are functional and aesthetic at the same time. In this community service, the lecturer and students collaborate with JMS Leather to design new products, from the identification of customer needs to the final prototype process. This process involved market analysis, in-depth interviews, customer surveys, and need-based design development. The designs are designed to be more minimalist, yet still functional to address the preferences of a wider market. With this approach, the program is expected to produce products that are innovative, attractive, and able to meet customer needs. In addition, this collaboration also aims to increase student creativity in applying product design knowledge practically. This method includes collecting data through Google Forms surveys to understand consumer needs and developing product prototypes. After obtaining the survey results, continue by processing the data and design ideas discussion with JMS Leather. The output is the product prototype and training JMS Leather about the process of product development and final prototype.